Little Joe [videorecording (DVD)] - Hausner, Jessica; Beecham, Emily, 1984-; Whishaw, Ben, 1980-; Fox, Kerry; Connor, Kit, 2004- (Magnolia Home Entertainment, 2020)
Alice is a dedicated senior plant breeder at a corporation engaged in developing new species; when she engineers a special flower that can induce happiness, she smuggles one home as a gift for her son. As the plant grows and changes her son Joe's behavior, it becomes clear that "Little Joe" -- as the plant is called -- may have harmful side effects.